2018
DOI: 10.1103/physrevb.97.214424
|View full text |Cite
|
Sign up to set email alerts
|

Weak magnetic anisotropy in GdRh2Si2 studied by magnetic resonance

Abstract: The antiferromagnetically (AFM) ordered state of GdRh2Si2 which consists of AFM-stacked ferromagnetic layers is investigated by magnetic resonance spectroscopy. The almost isotropic Gd 3+ paramagnetic resonance becomes anisotropic in the AFM ordered region below 107 K. The emerging internal anisotropic exchange-fields are still small enough to allow an investigation of their magnetization dynamics by using a standard microwave-frequency magnetic resonance technique. We could characterize this anisotropy in det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…(3)). They are remarkably close to those of Gd metal 18 , and the corresponding anisotropy fields reach 0.24 T, in good agreement with results by Sichelschmidt et al 31 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…(3)). They are remarkably close to those of Gd metal 18 , and the corresponding anisotropy fields reach 0.24 T, in good agreement with results by Sichelschmidt et al 31 .…”
Section: Resultssupporting
confidence: 91%
“…42 (similarly to Ref. 31 ) as 𝜔 0 = 2𝛾𝐵 𝐴 , with 𝛾 = 𝑔𝜇 𝐵 /ℎ and 𝑔 = 2 for Gd, in which 𝜇 𝐵 is Bohr's magneton and ℎ is Planck's constant. Finally, for a simple estimate of the constant 𝐾, we use the relation 𝐵 𝐴 = 𝐾/𝑚, in which 𝑚 is the total Gd 4f moment (𝜇 𝐵 𝑔 𝐽 𝐽,) and 𝑔 𝐽 is the Landé factor.…”
Section: Anisotropy Potentialmentioning
confidence: 99%
“…The comparison of the magnetic interactions occuring in the Rh and the Ir compounds will be a task for future work. Further studies of HoIr 2 Si 2 to investigate its magnetic structure using resonant inelastic X-ray scattering (RIXS) [18] or electron spin resonance (ESR) [19,20] are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, figure 1 shows only one of the magnetic domains and the other three domains are obtained by rotating all the depicted spin vectors by 90 • , 180 • or 270 • about the c-axis. The ESR in GdRh 2 Si 2 could be followed far inside the ordered regime [2], both at X-band and Q-band frequency. High-field ESR therefore seems unnecessary in this system and it is the aim of this work to quantify both terms of magnetocrystalline anisotropy at several temperatures T < T N using a conventional ESR setup.…”
Section: Introductionmentioning
confidence: 99%
“…Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI. spotlight, because previous works showed that its magnetism can excellently be described by a mean-field model together with an Ising-chain model [1] and it has been established experimentally that its anisotropy is well accessible by means of electron spin resonance (ESR) [2].…”
Section: Introductionmentioning
confidence: 99%